2013
DOI: 10.1155/2013/684353
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Parameters of Endurance Horses Pre- Compared to Post-Race, Correlated with Performance: A Two Race Study from Scandinavia

Abstract: Few studies have investigated the physiological parameters of endurance horses in Scandinavia. Hence, this two race study has focused on the effects of endurance racing in terms of equine clinicopathological blood parameters, heart score, and fluid use. Race A involved 15 horses (120 km). Two pre- and one post-race blood samples were taken, body condition score was assessed in triplicate pre-race, and an ECG was used to determine heart score. Race B involved 16 horses (65–120 km). One pre- and two post-race bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 23 publications
8
24
0
5
Order By: Relevance
“…No significant changes were observed in the plasma chloride concentrations of the horses which participated in this trial (P > 0.05). These chloride concentrations are similar in range to values reported by Larsson et al (2013), although in some instances, they identified preand post-race differences in the plasma chloride concentrations of endurance horses (P < 0.05). White et al (1991) found plasma chloride concentrations of Thoroughbred race horses that raced for a time of approximately 1-2 min to be significantly lower than resting levels, whereas Piccione et al (2007) observed a significant, extended increase in plasma chloride concentrations in horses exercised for 1 h. As compared with resting levels, Assenza et al (2014) observed significantly reduced serum chloride concentrations in horses that took part in a 3 d jumping competition; however, when the conditions were repeated a week later, the serum chloride concentrations increased and were not significantly different from resting levels.…”
Section: Resultssupporting
confidence: 86%
“…No significant changes were observed in the plasma chloride concentrations of the horses which participated in this trial (P > 0.05). These chloride concentrations are similar in range to values reported by Larsson et al (2013), although in some instances, they identified preand post-race differences in the plasma chloride concentrations of endurance horses (P < 0.05). White et al (1991) found plasma chloride concentrations of Thoroughbred race horses that raced for a time of approximately 1-2 min to be significantly lower than resting levels, whereas Piccione et al (2007) observed a significant, extended increase in plasma chloride concentrations in horses exercised for 1 h. As compared with resting levels, Assenza et al (2014) observed significantly reduced serum chloride concentrations in horses that took part in a 3 d jumping competition; however, when the conditions were repeated a week later, the serum chloride concentrations increased and were not significantly different from resting levels.…”
Section: Resultssupporting
confidence: 86%
“…This statement is consistent with the results of several studies which examined the effect of high-intensity exercise on the plasma SAA concentration in horses undergoing different types of training. Larsson et al (2013) have reported that the SAA concentration increase significantly by more than 1800 %, in horses participating in a 120 km endurance ride, in comparison to the resting values. T0 -at rest, T1 -immediately after the end of exercise, T2 -30 minutes after the end of the effort, T3 -24 hours after the first sampling a,b -means marked with different superscripts differ at p!0.05 !…”
Section: Discussionmentioning
confidence: 91%
“…CORT is frequently used to assess stress levels induced by exercise [70,71]. Different studies have been carried out in relation to stress in horses such as the load stress in tow [61], participation in equestrian dressage competition [72][73][74], competition of resistance [75] jumping [76], tourist driving and education [77]. It has been shown that moderate exercise in horse increases CORT by up to 29% compared to baseline levels through the stress response.…”
Section: Exercisementioning
confidence: 99%